Emotional School Engagement and Psychiatric Symptoms among 6-9-Year-old Children with an Immigrant Background in the First Years of School in Finland - Heidi Parviainen; Päivi Santalahti; Olli Kiviruusu (SPRINGER, 2022)
The aim of this study is to examine emotional school engagement and psychiatric symptoms among 6-9-year-old children with an immigrant background (n = 148) in their first years of school compared to children with a Finnish native background (n = 2430). The analyzed data consisted of emotional school engagement measures completed by children and Strengths and Difficulties Questionnaires completed by both parents and teachers. Children with an immigrant background had lower self-reported emotional school engagement than children with a native background with reference to less courage to talk about their thoughts in the class and more often felt loneliness. Further, they reported that they had more often been bullies and seen bullying in the class. Children with an immigrant background had more emotional symptoms and peer problems reported by parents than children with a native background. However, teachers did not report any significant differences.